Evaluasi dan Strategi Keberlanjutan Pasar Lingsir Wengi untuk Mitigasi Ketergantungan Pinjaman Ilegal - Ahmad Faizal; Hari Purnomo (Jurnal Manajemen dan Ilmu Administrasi, 2026)
This study aims to evaluate the optimization of the Lingsir Wengi MSME Market in Temuguruh Village as an economic empowerment program designed to overcome the community's dependence on bank plecit practices (illegal loans). Using a qualitative method with a case study approach, this research analyzes the supporting and inhibiting factors that influence the market's sustainability. The results indicate that functionally, the Lingsir Wengi Market has played a significant role in providing alternative livelihoods and creating economic independence, which ultimately reduces the practice of usury-based loans among the community. However, in the aspect of program management and sustainability, the market faces several serious challenges. The main inhibiting factors include the absence of a formal organizational structure or management team fully responsible for the market, lack of product innovation leading to visitor boredom, and fluctuations in the number of business actors. Meanwhile, strong supporting factors are the strategic location, full support from the Village Government, and the enthusiasm of the local community. Based on these findings, the novelty of this research lies in formulating a sustainability strategy based on local wisdom, which includes the establishment of a management team, strengthening digital marketing, and MSME human resource training to ensure long-term program effectiveness. The implication of this study is a policy recommendation emphasizing the importance of managerial professionalism in community-based economic empowerment to ensure program optimization and prevent the community from non-Sharia economic practices.